Design and Development of a Web-Based Tourism Information System for Tolikara Regency Using Codeigniter 4 - Moses Kogoya (Jurnal Indonesia Sosial Sains, 2026)
Trikala is an area with natural and cultural attractions such as waterfalls, agriculture and mountains. Many tourists want to visit these places but are limited by the difficulty of getting clear information such as good places and accommodation. The purpose of this research is to design a tourism system that uses a website to provide visitors, 360-degree panoramas, maps, and detailed descriptions of tourist attractions in Trikala to visitors and future visitors. Data collection methods include observation, interviews, and literature reviews. The method used to design this system is the waterfall method. The system testing method is black box testing. The results of the study concluded that using the Trikara Regional Tourism Information System based on the designed location can help users stay informed about the sights and attractions of Trikara district, as well as visit carefully planned places without fear or disappointment. The study concludes that the web-based tourism information system for Tolikara Regency can effectively help users access accurate and up-to-date information about tourist destinations, enabling them to plan their visits carefully without fear or disappointment. Furthermore, the system contributes to promoting local tourism potential and supporting economic development in the region.